Enzymatic properties and mutational studies of chalcone synthase from Physcomitrella patens - Raja Abdul Rahman, Raja Noor Zaliha; Zakaria, Iffah Izzati; Salleh, Abu Bakar; Basri, Mahiran (MDPI, 2012)
PpCHS is a member of the type III polyketide synthase family and catalyses the synthesis of the flavonoid precursor naringenin chalcone from p-coumaroyl-CoA. Recent research reports the production of pyrone derivatives using either hexanoyl-CoA or butyryl-CoA as starter molecule. The Cys-His-Asn catalytic triad found in other plant chalcone synthase predicted polypeptides is conserved in PpCHS. Site directed mutagenesis involving these amino acids residing in the active-site cavity revealed that the cavity volume of the active-site plays a significant role in the selection of starter molecules as well as product formation. Substitutions of Cys 170 with Arg and Ser amino acids decreased the ability of the PpCHS to utilize hexanoyl-CoA as a starter molecule, which directly effected the production of pyrone derivatives (products). These substitutions are believed to have a restricted number of elongations of the growing polypeptide chain due to the smaller cavity volume of the mutant’s active site.